Procesnopravni vidiki reševanja delovnih sporov v luči 25 letnice delovnih in socialnih sodišč v Republiki Sloveniji - Kogej Dmitrovič, Biserka (Delavci in delodajalci, 2019)
The paper presents an overview of the labour dispute settlements in Slovenia before the specialized courts. Already in the previous state regulation, the resolution of labour disputes took place before the labour courts according to a special procedure adapted to this type of disputes. In order to resolve labour disputes, 25 years ago the Republic of Slovenia established specialised labour and social courts and laid down a special procedure for their settlement, which was thereafter changed several times. Today, the procedure in labour disputes is increasingly approaching the classical civil procedure.
Keywords: Civil Procedure Act; competent court; delovna razmerja; delovni spori; Labour and Social Courts Act; labour dispute; labour relationships; pristojno sodišče; procedural provisions; specific features of labour disputes; zakon o delovnih in socialnih sodiščih; zakon o pravdnem postopku